Entrepreneurship of Operational Managers of Small Business Groups in Bogor District by Identifying the Strength of The Influence of Innovativeness, Organizational Culture and Job Satisfaction - Nanda Hidayati; Didik Nutosudjono; Widodo Sunaryo (West Science Business and Management, 2023)
This study looks primarily at the impact of job happiness, organizational culture, and innovativeness on the entrepreneurship of operational managers of small business groups in Bogor Regency. By examining the impact of organizational culture and innovativeness on the entrepreneurship of operational managers and using work satisfaction as an intervening variable, this study seeks to enhance the entrepreneurship of these managers. In Bogor Regency Region 2, data from 270 operational managers of SMEs were gathered for this study. The results of this investigation provide credence to the theory that inventiveness directly benefits entrepreneurship. This study demonstrates how innovation fosters innovation in processes, products, services, and organizations, all of which positively and directly impact entrepreneurship.